Schiller in Dostoevsky’s Works: Eleusinian Mysteries in The Brothers Karamazov - Tatyana A. Kasatkina (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
Since his early youth Dostoevsky valued Schiller as a person whoAbstract: Since his early youth Dostoevsky valued Schiller as a person whoopened his eyes to many things that the young man had only a presentment of; in hisimages Schiller offers some of the essential and deepest ideas of further Dostoevsky’sworks. These images played a very important role in creating the single conceptionalspace of the last Dostoevsky’s novel. Taking as an epigraph the only Evangelicepisode where Christ is talking to Hellenes having come to him, and in doing sousing the language and images of Eleusinian mysteries, at the same time Dostoevskyintroduced into his novel large quotes from Schiller’s “Eleusinian Feast” (translatedby Zhukovsky), connecting them in the reader's mind with “Ode to Joy”, and thuscreating a space for the manifestation of the main message of Eleusinian mysteriesincarnated in Christianity: the message of the fundamental unity of mankind, of adifferent human image, of a different human dimension, of the necessity of goingbeyond the reclusive terrene nature in order to achieve future life, as reclusiveness istreated by Dostoevsky as a perceptual error, a corruption of the “true outline of theman”.